The impact of implementing corporate social responsibility activities on employee commitment and employee identification in Taiwan - LI, PEI YU (2017)
Corporate Social responsibility (CSR) has been an important issue worldwide since the public has recognized the significance of human rights, environmental sustainability, social well-being. Numerous business organizations have deemed CSR activities as a critical strategy. In Taiwan, application of CSR activities has been an imperative practice to corporations. As the regulations, specific enterprises are required to issue CSR reports. According to Carroll (1979), the renowned definition of CSR, CSR was defined as those economic, legal, ethical and discretionary expectations from the society which corporations should meet. Based on the stakeholder theory, researchers have found that implementation of CSR activities benefits various stakeholders, such as customers, employees and investors. Furthermore, firms also apply CSR activities to be their sustainable advantage which is inimitable and non-substitutable by their competitors. In addition, implementation of CSR activities enforces firms’ relationship with different stakeholders (Carroll and Shaban, 2010). The aim of this study is to investigate the impact of CSR activities on employee commitment and employee identification. Employees are one of the critical stakeholders on the basis of stakeholder theory. As they usually perform the duty of CSR activities and they gain benefits from CSR activities as well. Application of CSR activity is an interplay between firm and employee. Existing research has provided evidence that CSR activities can enhance employee commitment which results in low turnover rate (Gupta,2017; Lee et al., 2013; Meyer and Allen, 1997). The research approach adopted survey questionnaire in this study. The findings of this research provide empirical evidence that firms implement CSR activities positively influence employee commitment in Taiwan. Furthermore, the findings also prove that employees identify with firm’s CSR activities, in turn, have influence on employee’s willingness to contribute to work. The main conclusion drawn from this study is that implementation of CSR activities has positive on employee commitment and identification in Taiwan. It is important that firms have a better insight of the impact of CSR on employee behaviour in Taiwan.